Testing a capacity-load model for hypertension: disentangling early and late growth effects on childhood blood pressure in a prospective birth cohort. - Carlos S Grijalva-Eternod; Debbie A Lawlor; Jonathan C K Wells (PLoS ONE)
Background In 2005, it was estimated that hypertension affected 26.4% of the adult population worldwide. By 2025, it is predicted that it will affect about 60% of adults, a total of 1.56 billion. Both pre- and postnatal growth patterns have been associated with later blood pressure (BP), but in contrasting directions. These inconsistent associations of growth during different developmental periods merit elucidation. We tested a theoretical model treating birth weight as a marker of homeostatic metabolic capacity, and childhood height, lean mass and fat mass as independent indices of metabolic load. We predicted that decreased capacity and increased load would be independently associated with increased BP. Methods and findings Data from the ALSPAC cohort on growth from birth to 7 years, and body composition by dual-energy X-ray absorptiometry and BP at 9 years, were analysed (n = 6579). Data were expressed as standard deviation scores (SDS) or standardised regression residuals (SRR). BP was independently and positively associated with each of height, lean mass and fat mass. In a joint model systolic BP was positively associated with conditional weight velocity [males 0.40 (95%CI: 0.37-0.44) & females 0.44 (95%CI: 0.40-0.47) SDS/SRR], but not birth weight [0.00 (95%CI: -0.03-0.04) & 0.03 (95%CI: -0.01-0.07) SDS/SDS]. Adjusting for height, lean mass and fat mass, the association of systolic BP and conditional weight velocity attenuated [0.00(95%CI: -0.09-0.08) & -0.06(95%CI: -0.14-0.03) SDS/SRR], whereas that with birth weight became negative [-0.10 (95%CI: -0.14-0.06) & -0.09 (95%CI: -0.13-0.05) SDS/SDS]. Similar results were obtained for diastolic BP and pulse pressure. Conclusions Consistent with our theoretical model, high metabolic load relative to metabolic capacity is associated with increased BP. Our data demonstrate the contribution of different growth and body composition components to BP variance, and clarify the developmental aetiology of hypertension.